Rural Poverty in Indonesia: Insights from Maqashid Syariah and Key Determinants - Nurul Izzah; Muhammad Ramadhan; Isnaini Harahap (Al-Qalam Institute, 2025)
Rural poverty remains a major development challenge in Indonesia because it is closely associated with limited access to economic resources, infrastructure, public services, and human development opportunities. This study aims to analyze the determinants of rural poverty in Indonesia from the perspective of maqashid sharia. Using panel data regression, this research examines the effects of village funds, village spending, the Village Development Index (VDI), the Islamic Human Development Index (IHDI), social capital, and economic growth on rural poverty. The model selection results indicate that the Fixed Effects Model (FEM) is the most appropriate estimation model. The findings show that village funds and IHDI have a positive and significant effect on rural poverty, while village spending, VDI, and economic growth have a negative and significant effect. Social capital, however, does not have a significant effect on rural poverty. These results suggest that rural poverty alleviation requires not only fiscal transfers, but also effective public spending, stronger village development, inclusive economic growth, and more substantive implementation of welfare-oriented policies in line with the principles of maqashid sharia. This study contributes to the rural poverty literature by offering a more comprehensive model that integrates economic, developmental, and Islamic welfare dimensions in the Indonesian context.